Safety of spinal radiotherapy in metastatic cancer patients receiving bevacizumab therapy. Issue 4 (April 2015) - Mbagui, Rodrigue; Langrand-Escure, Julien; Annede, Pierre; Mery, Benoite; Ceccaldi, Bernard; Guy, Jean-Baptiste; Falk, Alexander T.; Bauduceau, Olivier; Bosacki, Claire; Jacob, Julian; Helissey, Carole; Ferrand, Francois-Regis; et al.
<x xml:space="preserve">Abstract</x> We retrospectively assessed the outcome of patients receiving emergency spinal radiation therapy (RT) concurrently with bevacizumab. Clinical records of 18 consecutive patients receiving emergency spinal RT for symptomatic vertebral metastases during the course of bevacizumab-based therapy were examined. Patients were receiving biweekly bevacizumab combined with paclitaxel (n=17) or with docetaxel/carboplatin (n=1) or as a single agent (n=1) for advanced metastatic carcinoma. RT was delivered at doses of 30 Gy in 10 fractions (n=8), 20 Gy in five fractions (n=9) or 18 Gy in nine fractions (n=1). In 10 patients (56%), irradiation field encompassed the thoracic vertebrae. The median time interval between the bevacizumab infusion and the RT course was 1.5 days (0–8 days). The median follow-up was 8.3 months (2 days–42 months). A clinical benefit of RT was reported in 13 patients (72%), including four patients with complete pain relief. Two of the three patients with neurological impairment at the time of RT experienced a partial improvement in their symptoms. No pain recrudescence was reported within the irradiated field after RT completion. All toxicities were mild to moderate, with no acute toxicity reported in 13 patients (72%). No RT disruption was necessary because of acute toxicity. No delayed toxicity was reported within RT fields among 11 patients with at least 6 months of follow-up. Spinal RT during the course of bevacizumab-based therapy was not associated with the occurrence of unexpected adverse effects. This suggests that emergency RT should not be contraindicated in these patients, provided that doses and treatment volumes are defined carefully.